A Survey of Nursing Students at a selected Saudi University to evaluate their familiarity with Blood-Borne infection Prevention (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Transmission of infectious diseases via blood is known as blood borne pathogens. An infectious illness that may transmit from person to person by contact with contaminated blood or other bodily fluids. When healthcare personnel come into contact with infected patients, they are at high risk of contracting blood-borne pathogens via percutaneous exposure. The researchers in this study set out to determine how well nursing students at a few different schools in Riyadh, Saudi Arabia, understood how to avoid contracting blood-borne infections.